Distribution of nitric oxide-producing cells along spinal cord in urodeles - Mahmoud, Mayada A.; Fahmy, Gehan H.; Moftah, Marie Z.; Sabry, Ismail (Frontiers in Cellular Neuroscience, 2014)
Nitric oxide is a unique neurotransmitter, which participates in many physiological and pathological processes in the organism. There are little data about the neuronal nitric oxide synthase immunoreactivity in the spinal cord of amphibians. In this respect, the present study aims to investigate the distribution of nitric oxide producing cells in the spinal cord of urodele and to find out the possibility of a functional locomotory role to this neurotransmitter. The results of the present study demonstrate a specific pattern of NADPH-d labeling in the selected amphibian model throughout the spinal cord length as NADPH-d-producing cells and fibres were present in almost all segments of the spinal cord of the salamander investigated. However, their number, cytological characteristics and labeling intensity varied significantly. It was noticed that the NO-producing cells (NO-PC) were accumulated in the ventral side of certain segments in the spinal cord corresponding to the brachial and sacral plexuses. In addition, the number of NO-PC was found to be increased also at the beginning of the tail and this could be due to the fact that salamanders are tetrapods having bimodal locomotion, namely swimming and walking.